Intercropping cover crops with a poplar short rotation coppice: Effects on nutrient uptake and biomass production - Silvestri, Nicola; Giannini, Vittoria; Antichi, Daniele (Italian Journal of Agronomy, 2018)
The risks of soil erosion and nutrient leaching can be considered appreciable in short rotation coppices especially in the first growth phases because of the absence of any plant cover. The temporary intercropping with legumes or grasses used as cover crops can help to overcome these environmental issues. The present research work aims to evaluate the effects of the introduction of cover crops in a short rotation poplar (Populus deltoides W. Bartram ex Marshall) with two-year harvest cycle. The plantation was located in a Typic Xerofluvent, silty-loam soil of the coastal Central Italy. Two different species of cover crops, Trifolium subterraneum L. (TS) and Lolium perenne L. (LP), were compared along with an untreated control, colonised by spontaneous vegetation (CO). Several plant and soil parameters were evaluated: the above ground biomass and nutrient accumulation for the three different soil cover types, the nitrate and water content in two soil layers (0.00-0.30 and 0.30-0.60 m), the poplar yield and nutrient content in branches and leaves. TS returned to the soil about 70 kg ha–1 of nitrogen at the end of its biological cycle, thanks to the high N content (over 2%) and to the noticeable amount of dry matter produced (3.46 t ha–1 of dry matter). This value was considerably higher than those of the LP (23 kg ha–1 of N) or CO (10 kg ha–1). The different amount of nitrogen returned to the soil affected both nitrate concentration in topsoil (0.00-0.30 m) and accumulation of nitrogen in poplar organs. Concerning phosphorous, the differences among treatments were less evident and the amount of P returned to the soil ranged from 2 (CO) to 10 (TS) kg ha–1. However, the effect of soil cover type on P uptake in poplar was still appreciable. Generally, the soil water content was slightly affected by the soil cover types. Indeed, the differences between the cover crops and the control became significant only in the shallowest soil layer and over the summer season. In the first year, LP induced a significant decrease in poplar yield (10.1 t ha–1 of dry matter) in comparison with TS (14.7 t ha–1) and CO (13.4 t ha–1), whereas in the second year there were no significant differences among treatments due to the weak regrowth of cover crops. These results show how to make it feasible a long lasting coexistence between cover crops and SRC, a clever design of agro-forestry systems is therefore needed.